Respostas

A melhor resposta!
2014-02-01T17:17:39-02:00
x²-4x-10=11
x²-4x=11+10
x²-4x=21
x²-4x-21=0

Δ = b² -4ac
Δ = (-4)² -4 *1 * (-21)
Δ = 16 + 84
Δ = 100
x' = (-b + √∆)/ 2a
(-(-4) + 10)/2 * 1
(4 + 10)/2
14/2
7
x'' = (-b - √∆)/ 2a
(-(-4) - 10)/2 * 1
(4 - 10)/2
-6/2
-3

\[\boxed{S=-3,7}\]

1 5 1
  • PeH
  • Ambicioso
2014-02-01T17:32:19-02:00
Para achar as raízes desta equação, basta transformá-la da seguinte forma:

x^2 - 4x - 10 = 11 \\
x^2 - 4x - 10 - 11 = 0 \\
x^2 - 4x - 21 = 0

A partir daí:

x^2 - 4x - 21 = 0 \\\\
\bullet a = 1 \\
\bullet b = -4 \\
\bullet c = -21 \\\\
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \\\\
x = \frac{4 \pm \sqrt{16 - 4 \cdot 1 \cdot (-21)}}{2 \cdot 1} \\\\
x = \frac{4 \pm 10}{2} \\\\
x_1 = \frac{4 + 10}{2} = 7 \\\\
x_2 = \frac{4 - 10}{2} = -3 \\\\
\boxed{\text{S} = \{-3,7\}}
1 5 1